Paradigma Pembelajaran Daring Pendidikan Agama Hindu di Masa Pandemi Covid-19 Pada Program Studi Pendidikan Agama Hindu STAHN Mpu Kuturan Singaraja - Vivien Pitriani, Ni Rai; Diana Putra, I Gede Dedy (Jayapangus Press, 2023)
The impact of the Covid-19 pandemic has had a major impact on the world of education, this influence is a challenge for academics to realize national education goals through Hindu religious education. It is felt that it is very important to research the online learning paradigm in Hindu religious education during the Covid-19 pandemic which was carried out in the Hindu religious education study program STAHN Mpu Kuturan Singaraja. The purpose of this research is to find out the online learning paradigm, and to find out character strengthening through Hindu religious education during a pandemic. This research is a qualitative research that displays descriptive data consisting of words. An analysis was carried out based on the theory of social change, the theory of behaviorism and Technological Determinism. This study obtained the results, namely the problems faced by students when learning online were lectures getting bored quickly, constrained by cellular operator signals, reduced communication between students and lecturers, inadequate equipment, quota fees, communication with parents was not directed. The challenges faced are not accustomed to online and independent learning, limited internet network, internet access and electricity, lack of facilities and resources, non-conducive environment, children are enthusiastic with their friends, the ability of parents to accompany children to study is different. There is a digital education transition that is felt, namely before the pandemic learning was carried out face-to-face, during the pandemic it was carried out fully online, after the pandemic it is likely that offline and online systems will be implemented. The principles of online learning are learning is open, social, personal, augmented, multirepresented, and learning is mobile. Strengthening the character of students must be accustomed to carrying out positive habits starting at home from maintaining cleanliness and health, carrying out useful activities, praying diligently and respecting and being polite to parents.